The Way of Logic into Mathematics - Peckhaus, Volker (Theoria. Segunda Época (Seccion monografica Sobre la historia de la lógica matemática, hg. v. Luis Vega Reñon))
Abstract: Philosopher’s Index 31.3 (1997), 206; Zbl. Math. 914.01008 (L. Harkleroad). Rezensionen: MR 98c:01028 (E. Glas).

The Axiomatic Method and Ernst Schröder’s Algebraic Approach to Logic - Peckhaus, Volker (Philosophia Scientiae. Travaux d’histoire et de philosophie des science (Nancy) 1/3 (1996). 1–15 [erschienen im Juni 1997, = Actes du congrès International Poincaré – Nancy 1994; Bd. 2.2])

Application of Neural Networks for Control of Four-Quadrant Converters in Railway Propulsion Systems Applications of Neural Adaptive Control Technology - Scheffler, Sebastian; Böcker, Joachim (Applications of Neural Adaptive Control Technology)

Witold Marciszewski/Roman Murawski. Mechanization of Reasoning in a Historical Perspective. Amsterdam/Atlanta, GA: Rodopi 1995. (Poznań Studies in the Philosophy of the Sciences and the Humanities; 43) - Peckhaus, Volker (Modern Logic)

Ein automatisiertes Verfahren zur Off-line-Identifikation der elektrischen Parameter von pulswechselrichtergespeisten Asynchronmotoren - Ruff, M.

Beiträge zur Entwicklung von Gleichstromumrichtern mit geringer Ausgangsspannung - Fiedler, A.

Excitons with anisotropic effective mass - Schindlmayr, Arno (European Journal of Physics)
We present a simple analytic scheme for calculating the binding energy of excitons in semiconductors that takes full account of the existing anisotropy in the effective mass, as a complement to the qualitative treatment in most textbooks. Results obtained for excitons in gallium nitride form the basis for a discussion of the accuracy of this approach.

Violation of particle number conservation in the GW approximation - Schindlmayr, Arno (Physical Review B)
We present a nontrivial model system of interacting electrons that can be solved analytically in the GW approximation. We obtain the particle number from the GW Green’s function strictly analytically, and prove that there is a genuine violation of particle number conservation if the self-energy is calculated non-self-consistently from a zeroth order Green’s function, as done in virtually all practical implementations. We also show that a simple shift of the self-energy that partially restores self-consistency reduces the numerical deviation significantly.

[Rez. v.] Luigi Marino. Praeceptores Germaniae. Göttingen 1770–1820. Aus dem Italienischen v. Brigitte Szabó-Bechstein. Göttingen. Vandenhoeck & Ruprecht 1995 - Süßmann, Johannes (Archiv für Sozialgeschichte)

[Rez. v.] Ingeborg Cleve: Kunst und Konsum. Kulturpolitik als Wirtschaftspolitik in Frankreich und Württemberg (1805–1845). Göttingen. Vandenhoeck & Ruprecht 1996 - Süßmann, Johannes (Archiv für Sozialgeschichte)

Resonant transition switching welding power supply - Fröhleke, N.; Mundinger, H.; Beineke, S.; Wallmeier, P.; Grotstollen, H. (Proceedings of the IECON'97 23rd International Conference on Industrial Electronics, Control, and Instrumentation (Cat. No.97CH36066))

A critical comparison of boost-topologies for single-phase switched mode rectifiers - Wallmeier, P.; Fröhleke, N.; Richter, J.; Ide, P.; Grotstollen, H. (Proceedings of Power and Energy Systems in Converging Markets)

STARBIST: Scan Autocorrelated Random Pattern Generation - Tsai, Kun-Han; Hellebrand, Sybille; Marek-Sadowska, Malgorzata; Rajski, Janusz (34th ACM/IEEE Design Automation Conference (DAC'97))

Die Bild-Macht des erhabenen Gefühls. Ästhetische Theorie und literarische Praxis des Erhabenen im 18. Jahrhundert - van Laak, Lothar (Ästhetische und religiöse Erfahrungen der Jahrhundertwenden I: um 1800)

Christoph Martin Wielands Peregrinus Proteus als Satyrspiel der Aufklärung - van Laak, Lothar (Sprache und Literatur in Wissenschaft und Unterricht 80)

Die genetische Epistemologie Jean Piagets in der Perspektive der Vernunftkritik - Scharlau, Ingrid (Grundlinien der Vernunftkritik)

Cyberspace - Scharlau, Ingrid (Deep Storage - Arsenale der Erinnerung - Sammeln, Speichern, Archivieren in der Kunst)

Piaget lesen - Scharlau, Ingrid (Information Philosophie)

"Die Erscheinung der Gewalt ist seltsam schön". Caravaggio als Ikone tödlicher Obsession bei Christoph Meckel und Christoph Geiser - Öhlschläger, Claudia (Ikonen des Begehrens. Bildsprachen der männlichen und weiblichen Homosexualität in Literatur und Kunst)

Körper-Gedächtnis-Schrift. Der Körper als Medium kultureller Erinnerung